2-Iodoxybenzoic acid ditriflate: the most powerful hypervalent iodine(v) oxidant. Issue 54 (18th June 2019) - Yusubov, Mekhman S.; Soldatova, Natalia S.; Postnikov, Pavel S.; Valiev, Rashid R.; Yoshimura, Akira; Wirth, Thomas; Nemykin, Victor N.; Zhdankin, Viktor V.
Abstract : A new powerful hypervalent iodine(v ) oxidant, a ditriflate derivative of 2-iodoxybenzoic acid (IBX), was prepared by the reaction of IBX with trifluoromethanesulfonic acid and characterized by single crystal X-ray crystallography. Abstract : A ditriflate derivative of 2-iodoxybenzoic acid (IBX) was prepared by the reaction of IBX with trifluoromethanesulfonic acid and characterized by single crystal X-ray crystallography. IBX-ditriflate is the most powerful oxidant in a series of structurally similar IBX derivatives which is best illustrated by its ability to readily oxidize hydrocarbons and the oxidation resistant polyfluoroalcohols.